Migration and gender dynamics of irrigation governance in Nepal - Meinzen-Dick, Ruth S.; Pradhan, Prachanda; Zhang, Wei (International Food Policy Research Institute, 2021)
Nepal has a long history of irrigation, including government and farmer-managed irrigation systems that are labor- and skill-intensive. Widespread male migration has important effects on Nepalese society. How institutions such as Water Users’ Associations (WUAs) respond and adapt, is therefore critical to the understanding of rural transformation and the likely impact on gender equality, food production, and rural livelihoods. This paper examines the effects of male migration on institutional change in WUAs, women’s roles, technological change, and outcomes affecting effectiveness of irrigation systems based on a mixed methods study, combining a phone survey of 336 WUA leaders from all provinces in Nepal with qualitative data from case studies in 10 irrigation systems. Results indicate WUAs have adapted rules to increase women’s participation and monetize the contributions for maintenance. Women exercise agency in whether and how to interact with WUAs. Mechanization has reduced the need for some male labor, though the ability to mechanize is limited by hilly terrain and small plot sizes. Overall, systems are adapting to male migration, with relatively low idling of land or labor shortages causing deterioration of the systems, though there are concerns with the high levels of women’s labor burdens.